Penerapan nilai-nilai pancasila di era modern - Ikhsan, Muhammad Fatikhul (Maliki Interdisciplinary Journal, 2025)
Philosophically, Pancasila is the Weltanschauung (worldview) and Philosophische Grondslag (ethical foundation) that unifies the nation's noble values—Belief in God, Just and Civilized Humanity, the Unity of Indonesia, Democracy Guided by the Wisdom of Deliberation among Representatives, and Social Justice—into an organic whole. It functions as an open ideology that provides the state with ethical direction and purpose. Practically, Pancasila is an operational guide (way of life) that directs all aspects of life, ranging from the formulation of public policy and law enforcement to social interaction. A comprehensive understanding and practice of the essence of Pancasila is vital for maintaining national unity, mitigating conflicts, and realizing a just and civilized society amidst diversity. Thus, strengthening the understanding and comprehensive application of Pancasila is not only a philosophical necessity but also a practical requirement in facing contemporary social, political, and cultural dynamics. Pancasila remains relevant as the moral and operational foundation of the nation, as well as a key pillar in building a harmonious, democratic, and civilized Indonesian society.